Role of lipoxygenase products in the effects of angiotensin II in the isolated aorta and perfused heart of the rat - J. P. M. Dam; E. van den Worm; W. Vleeming; M. J. Post; A. J. Porsius; J. Wemer (Hindawi Limited, 1995)
The objective of this study was to determine whether arachidonate metabolites are involved in the vasoconstrictive effects of angiotensin II in rats. In the isolated perfused heart, dexamethasone (4 mg/kg) significantly suppressed the maximal decreases in coronary flow induced by angiotensin II and vasopressin (reference drug). In the heart, the nonselective lipoxygenase inhibitor nordihydroguaiaretic acid (NDGA, 1 μM) markedly suppressed the angiotensin II-induced decreases in coronary flow. NDGA (10 μM) inhibited both angiotensin II- and methoxamine- (reference drug) induced contractions in aortic rings with (in the presence of L-NAME) and without endothelium. In the heart, the leukotriene synthesis inhibitor MK-886 (0.3 μM) significantly reduced the maximal effects to angiotensin II, but the leukotriene antagonist FPL 55712 (0.1 and 0.3 μM) had no effect. We conclude that in the isolated perfused rat heart angiotensin II-induced decreases in coronary flow are in part mediated by Hpoxygenase products, which might be derived from the 5-Hpoxygenase pathway, but are probably not leukotrienes. Furthermore, endothelium independent Hpoxygenase products mediate part of the contractile responses to angiotensin II in the isolated rat aorta.